FLORISTIC AND STRUCTURE IN AREA OF SEASONAL DECIDUOUS FOREST IN THE REGION OF THE ALTO URUGUAI, RS - Lambrecht, F. R.; Dallabrida, J. P.; Trautenmüller, J. W.; de Carli, L.; Burgin, M. R. B.; de O. Fortes, F. (Revista Brasileira de Engenharia de Biossistemas, 2016)
The study aimed to carry out the floristic analysis and horizontal and vertical structures in a fragment of Deciduous Forest (FED) in the region of Alto Uruguai in Frederico Westphalen, RS, Brazil. It conducted a census in a sample area of 10.000 m², subdivided en 100 subplots 10x10m. Held measurement and identification of all individuals of tree species with circumference at breast height (CBH) ≥ 31cm. With the obtained data, calculations were performed of density (D), frequency (F), dominance (Do), importance value index (IVI) coverage value index (IVC) and the stratification of individuals. The greater number of species concentrated in the family Fabaceae (10) and the largest number of individuals in the family Meliaceae (147 or 25.3%). Trichilia claussenii C. DC., Nectandra megapotamica (Spreng.) Mez, Achatocarpus praecox Griseb and Eugenia rostrifolia D. Legrand represented 38.28% of the relative density and Holocalyx balansae Micheli, Trichilia claussenii, Nectandra megapotamica, Cordia americana (L.) Gottshling & J.E.Mill., Phytolacca dioica L., Achatocarpus praecox, and Eugenia rostrifolia represented 50.5% of relative dominance. Considering the vertical structure, the seven most common species have a greater number of individuals in the middle stratum. It is concluded that the forest is at an intermediate stage of succession.